Framework to assess the level of readiness for TQM implementation in girls' secondary schools in Saudi Arabia - Hassan, Asma Abdullah (Cranfield University, 2016)
The Kingdom of Saudi Arabia (SA) set out its Vision 2030 of itself as a significant Knowledge Economy to position itself competitively in the world and in the Gulf region. The Government charged the education sector to prepare young people and build the creativity, innovation and technical skills for the country’s future. The Ministry of Education (MOE) selected TQM and has made strategic investments to achieve this strategic transformation in education. Despite this substantial investment in the infrastructure, teaching skills, information technology and advancement programmes for women to enter the workplace, the implementation of TQM has not so far delivered the outcomes expected in secondary schools (Bank, 2008; Chapman and Miric, 2009; TIMSS, 2011). This research proposes that a programme that primarily focuses on the hard aspects of change, without participatory leadership and without integrating the people concerned (as a soft programme would), cannot achieve sustainable transformation. An empirical study was designed to investigate staff perception of TQM implementation in girls’ secondary schools in the Kingdom. The 525 respondents from 61 schools in five districts of Riyadh suggest that the most pivotal critical success factors (CSFs) limiting the development of TQM culture were Top Management Commitment; Training; Tools and Techniques; and Reward and Recognition. The perception results were then used as the baseline to design a model that integrates the hard and soft CSFs of TQM in five stages of maturity. This assessment model could be used to support the schools and the MOE in objectively assessing the readiness of schools to implement TQM and identify the next major obstacles to reaching the next stage. The design approach of a maturity model is innovative in using context perception data as the baseline for designing the stages of maturity and the success factors the progress of change, making its use appropriate for the girls’ schools in the Kingdom of Saudi Arabia.
Keywords: CSF; Obstacles; Maturity; Influencing Variables; Culture; Capability; Continuous Improvement